Thioreductase-Containing Epitopes Inhibit the Development of Type 1 Diabetes in the NOD Mouse Model - Malek Abrahimians, Elin; Vander Elst, Luc; Carlier, Vincent A.; Saint-Remy, Jean-Marie (Frontiers in Immunology, 2016)
Autoreactive CD4+ T cells recognizing islet-derived antigens play a primary role in type 1 diabetes. Specific suppression of such cells therefore represents a strategic target for the cure of the disease. We have developed a methodology by which CD4+ T cells acquire apoptosis-inducing properties on antigen-presenting cells after cognate recognition of natural sequence epitopes. We describe here that inclusion of a thiol-disulfide oxidoreductase (thioreductase) motif within the flanking residues of a single MHC class II-restricted GAD65 epitope induces GAD65-specific cytolytic CD4+ T cells (cCD4+ T). The latter, obtained either in vitro or by active immunization, acquire an effector memory phenotype and lyse APCs by a Fas-FasL interaction. Further, cCD4+ T cells eliminate by apoptosis activated bystander CD4+ T cells recognizing alternative epitopes processed by the same APC. Active immunization with a GAD65 class II-restricted thioreductase-containing T cell epitope protects mice from diabetes and abrogates insulitis. Passive transfer of in vitro-elicited cCD4+ T cells establishes that such cells are efficient in suppressing autoimmunity. These findings provide strong evidence for a new vaccination strategy to prevent type 1 diabetes.